Tambach remixed: "Christians in South African society" - Senokoane, B. B. (HTS teologiese studies, 2007)
This article flows from the previous one, which analysed Karl Barth’s Tambach lecture in its original German context. It uses the musical metaphor of “remixing” to describe the recontextualising of Barth’s Tambach approach in contemporary South African society. After recontextualising the theological foundations of the Tambach lecture, Barth’s three viewpoints (regnum naturae, regnum gratiae, regnum gloriae) are recontextualised for South Africa, addressing the issue of poverty as an example.